Implementasi Re-design UI/UX Website Fumigasi Untuk Meningkatkan Customer Experience - Faisal Maulana Akbar; Ayouvi Poerna Wardhanie2; Tan Amelia (Journal of Applied Computer Science and Technology, 2023)
Fumigation website is a website owned by PT. Prana Argentum which is used as a platform for disseminating information related to pest control. However, based on interviews with company owners, there are some drawbacks such as the appearance of the website is not very user friendly, the information provided is difficult to find. This is also supported by the results of the UEQ pre-survey of website users, where the results of the 6 UEQ scale get the "bad" criterion, which means the low usability value of the website. This study aims to determine the suitability of the company's website in improving customer experience. To overcome the display problems on the website, a solution is needed, namely redesigning the UI/UX design using the double diamond methodology and usability testing along with UEQ. The result of this research is a redesign of the UI/UX design by adding new features such as a price quote feature, an appointment feature, and a transaction feature. To improve the customer experience, researchers also pay attention to the use of colors, fonts, language styles, to user-friendly navigation flows. In this study, two types of tests were carried out, namely usability testing with the Maze tools and UEQ testing. The usability testing results obtained a usability score of 87 which can be said to be good in terms of its usability value. Based on the results of the UEQ test, it is known that there is an increase in the mean value on all UEQ scales. It is proved that the highest mean value is on the perspicuity scale of 2.09 points and the lowest value is on the novelty scale with a value of 1.53 points. the results of the UI/UX website design of PT. Prana Argentum Corporation is classified as good, proper, and acceptable to users.